Entrepreneurial marketing and its impact on attracting customers (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Through this research, we are ready to determine the role of entrepreneurial marketing investigation by measuring its extended dimensions (remaining, discovering, focusing on opportunities, generating value, knowledge from resources, specific, specific) in attracting customers with its dimensions (trust, building relationships), as any research It must begin with a specific question, and this research is planning a question, which is (what is the role of entrepreneurial marketing in attracting customers), conducting research in a number of Iraqi Internet companies in the capital, Baghdad, extension B (Al-Jazeera Company, Harnes Company, Hala FTTG Company), The questionnaire was used as a tool for collecting data, and the size of the population on which the field study was conducted was the employees working in the mentioned companies, which numbered (275) individuals. Random A sample of (146) individuals was selected from the total number mentioned, and they are the final respondents to the research questionnaire, as the researcher relied on the descriptive approach. To complete this research, the statistical program (spss. v26) was used to analyze the data. One of the most prominent findings of the research is the presence of an impact of entrepreneurial marketing in attracting customers.